Discrete Notch signaling requirements in the specification of hematopoietic stem cells. (17th September 2014) - Kim, Albert D; Melick, Chase H; Clements, Wilson K; Stachura, David L; Distel, Martin; Panáková, Daniela; MacRae, Calum; Mork, Lindsey A; Crump, J Gage; Traver, David
Abstract Hematopoietic stem cells (HSCs) require multiple molecular inputs for proper specification, including activity of the Notch signaling pathway. A requirement for the Notch1 and dispensability of the Notch2 receptor has been demonstrated in mice, but the role of the remaining Notch receptors has not been investigated. Here, we demonstrate that three of the four Notch receptors are independently required for the specification of HSCs in the zebrafish. The orthologues of the murine Notch1 receptor, Notch1a and Notch1b, are each required intrinsically to fate HSCs, just prior to their emergence from aortic hemogenic endothelium. By contrast, the Notch3 receptor is required earlier within the developing somite to regulate HSC emergence in a non‐cell‐autonomous manner. Epistatic analyses demonstrate that Notch3 function lies downstream of Wnt16, which is required for HSC specification through its regulation of two Notch ligands, dlc and dld. Collectively, these findings demonstrate for the first time that multiple Notch signaling inputs are required to specify HSCs and that Notch3 performs a novel role within the somite to regulate the neighboring precursors of hemogenic endothelium.